Lipopolysaccharide-Induced Transcriptional Changes in LBP-Deficient Rat and Its Possible Implications for Liver Dysregulation during Sepsis. (30th December 2021) - He, Zhixiang; Song, Zichen; Meng, Leilei; Cheng, Wenhui; Huang, Fan; Zheng, Mao; Xu, Wenhui; Xiao, Rong; Fang, Haoshu; Zhu, Yaling
Abstract : Sepsis is an organ dysfunction caused by the dysregulated inflammatory response to infection. Lipopolysaccharide-binding protein (LBP) binds to lipopolysaccharide (LPS) and modulates the inflammatory response. A rare systematic study has been reported to detect the effect of LBP gene during LPS-induced sepsis. Herein, we explored the RNA sequencing technology to profile the transcriptomic changes in liver tissue between LBP-deficient rats and WT rats at multiple time points after LPS administration. We proceeded RNA sequencing of liver tissue to search differentially expressed genes (DEGs) and enriched biological processes and pathways between WT and LBP-deficient groups at 0 h, 6 h, and 24 h. In total, 168, 284, and 307 DEGs were identified at 0 h, 6 h, and 24 h, respectively, including Lrp5, Cyp7a1, Nfkbiz, Sigmar1, Fabp7, and Hao1, which are related to the inflammatory or lipid-related process. Functional enrichment analysis revealed that inflammatory response to LPS mediated by Ifng, Cxcl10, Serpine1, and Lbp was enhanced at 6 h, while lipid-related metabolism associated with C5, Cyp4a1, and Eci1 was enriched at 24 h after LPS administration in the WT samples. The inflammatory process was not found when the LBP gene was knocked out; lipid-related metabolic process and peroxisome proliferator-activated receptor (PPAR) signaling pathway mediated by Dhrs7b and Tysnd1 were significantly activated in LBP-deficient samples. Our study suggested that the invading LPS may interplay with LBP to activate the nuclear factor kappa B (NF- κ B) signaling pathway and trigger uncontrolled inflammatory response. However, when inhibiting the activity of NF- κ B, lipid-related metabolism would make bacteria removal via the effect on the PPAR signaling pathway in the absence of LBP gene. We also compared the serum lactate dehydrogenase (LDH) and alkaline phosphatase (ALP) levels using the biochemistry analyzer and analyzed the expression of high mobility group box 1 (HMGB1) and cleaved-caspase 3 with immunohistochemistry, which further validated our conclusion.